STUDI LITERATUR : ANALISIS PEMANFAATAN WORDWALL SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Awalina Barokah; Inayah Safitri; Nabilah Ayu Lestari; Ita Rosita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low learning motivation of students, which affects the success of the learning process. This problem can be overcome by utilizing interactive learning media such as Wordwall, which can support students in increasing learning motivation. This research aims to find out how effective the use of Wordwall as a learning medium is in increasing students' learning motivation. The method used in this research is literature study. The results of the research show the importance of using interactive learning media such as Wordwall in the teaching and learning process. The use of Wordwall can increase students' learning motivation by making the learning process more interesting, interactive and fun and has a positive impact on improving learning outcomes.